Gait Analysis of Patients Suffering From Hallux Valgus. Issue 1 (19th August 2016) - Ito, Naoya; Nishimura, Akinobu; Nakazora, Shigeto; Kato, Ko; Sudo, Akihiro
Category: Midfoot/Forefoot Introduction/Purpose: Hallux valgus that is defined as HVA (hallux valgus angle) >20 is one of the most common forefoot problems and can lead to alterations of the plantar pressure pattern. In addition, it can cause clinically gait alterations. Hence, we investigated the plantar pressure pattern and the gait-related factors using the gait analyzer. The purpose of this study was to examine the relationship between gait alterations or motor function and hallux valgus deformity. Methods: In 2009, we examined 309 inhabitants (male, 105; female, 204; age, >65 years) of Miyagawa village in Mie, Japan and compared the plantar pressure pattern between the subjects who has hallux valgus (HVA, >20; n=88) and those who does not have hallux valgus (HVA, < 20; n = 221). Furthermore, we compared gait-related factors among mild group (20< HVA < 30; n=88), moderate group (30< HVA < 40; n=24), and severe group (HVA, >40; n=9). If the right and left hallux valgus varied in severity, we selected severe side. The plantar pressure pattern and the gait-related factors such as stride, step width, foot angle (Figure 1), and gait speed were measured using the gait analyzer (Walk way MW 1000; Anima, Tokyo, Japan). Statistical analyses were performed using t-test, Chi-Square test, or logistic analysis adjusted age, gender and height. P < 0.05 was considered significant. Results: The average weight and height of hallux valgus group were significantly lower, and age of hallux valgus group were significantly higher than those of normal group. About the plantar pressure pattern, ratio of the subjects in hallux valgus group who can use the hallux ball in toe off were significantly less than those of normal group. However, the gait-related factors were not significantly different between 2 groups. On the other hand, when we compared by severity, step width tended to increase with progression of hallux valgus. Moreover, stride, gait speed, and foot angle of severe group were the lowest among 4 groups (normal, mild, moderate, and severe). Especially stride of severe group was significantly lower than those of other 3 groups. Conclusion: Mild hallux valgus can cause alterations of the plantar pressure pattern, but didn't cause motor functional decline. However, when hallux valgus become severe, hallux valgus can cause not only gait alterations but also motor functional decline.